THE ROLE OF EMPLOYEE EXPERIENCE IN IMPROVING EMPLOYEE RETENTION IN THE DIGITAL AGE: A REVIEW OF THE LATEST LITERATURE - SRI NDARU ARTHAWATI; Eloh Bahiroh (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Digital transformation has fundamentally changed the landscape of the world of work, giving rise to new challenges in employee retention that cannot be addressed through technological investment alone. This article aims to examine the strategic role of Employee Experience (EX) in enhancing employee retention in the digital age through a synthesis of the latest literature. The research method employed is a literature review using a narrative-systematic approach, with data sources drawn from scientific journal articles, books and research reports. The findings indicate that Employee Experience plays a central role in employee retention through two key dimensions: Digital Employee Experience (DEX) and Holistic Employee Journey Design. DEX serves as the foundation for retention by reducing digital friction, enhancing digital wellbeing (Wellbeing 2.0), and creating technology-enabled interactions that support productivity and job satisfaction. Meanwhile, Holistic Employee Journey Design strengthens engagement and loyalty through integrated experience design across the employee lifecycle, encompassing effective onboarding, continuous career development, an inclusive organisational culture, work-life balance, and meaningful recognition systems. Organisations that have successfully integrated these two dimensions report a retention increase of up to 32 per cent over a six-month period. The managerial implications of this research emphasise the importance of an integrated, data-driven approach to managing EX, whereby organisations need to regularly audit the quality of DEX, gather employee feedback through the Voice of the Employee, and make continuous adjustments based on the insights gained. The conclusion of this study is that Employee Experience is no longer a supplementary initiative, but rather a strategic imperative that determines an organisation’s sustainability and competitive advantage in the digital age.